2019
DOI: 10.1002/pssa.201900540
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nitrogen Adsorption of Doped Ta on Characteristics of SiNx‐Based Resistive Random Access Memory

Abstract: The characteristics and conductive mechanism of Ta/SiN x /Ta:SiN x /SiN x /Pt resistive random access memory (RRAM) are investigated. Compared with Pt-doped devices with the same structure, the Ta-doped devices produce lower operation current in a high resistance state and a larger on/off radio. Furthermore, reliability tests show that the Ta-doped RRAM has good data retention ability and endurance. Ta clusters are observed in the Ta-doped SiN x layer through the transmission electron microscope. Also, the X-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Eqn (2) suggests that the validity of the Schottky mechanism can be confirmed by examining the linearity of a graph. 29 Fig. 10(a) clearly shows a linear relationship, which is consistent with the prediction of eqn (1).…”
Section: Resultssupporting
confidence: 86%
“…Eqn (2) suggests that the validity of the Schottky mechanism can be confirmed by examining the linearity of a graph. 29 Fig. 10(a) clearly shows a linear relationship, which is consistent with the prediction of eqn (1).…”
Section: Resultssupporting
confidence: 86%
“…In order to understand the difference of AlO x CL effect between dopant-free HfO x and doped-HfO x films, the HfZrO x MFM capacitors with different CL thicknesses were also carried out for a performance comparison. From thermodynamic analysis, the Gibbs free energies for ZrO 2 , HfO 2 , Al 2 O 3 and TaN are -1100 kJ/mol, -1010.8 kJ/mol, -1500 kJ/mol, and -604.96 kJ/mol, respectively [23], [24]. We can understand that the interface reaction at the TaN/HfO x and TaN/ZrO x interface is more significant than that of TaN/AlO x interface.…”
Section: Resultsmentioning
confidence: 89%
“…We reported that SiN x ‐based RRAM locally doped with Ta in the middle of the dielectric layer has high on/off radio characteristics. [ 22 ]…”
Section: Introductionmentioning
confidence: 99%
“…We reported that SiN x -based RRAM locally doped with Ta in the middle of the dielectric layer has high on/off radio characteristics. [22] A recent study has shown that doping at different positions in the oxide RS layer affects device performance. [23] Since typical conductive channels have a tapered structure, local doping of metals in the RS layer can make a more regular concentration of connections and disconnections of CFs locally, improving the device's performance.…”
Section: Introductionmentioning
confidence: 99%